Analisis Manajemen Risiko Pada Toko Casual Brezzy Reseller Sepatu Adidas Impor Menggunakan Pendekatan ISO 31000 - Berdhy Ursila Djamil; Amelia Rahmadani; Ahmad Ryansyah; Wafiayati Nuramrina; Alfiana (Indo Publishing, 2025)
This study aims to analyze the implementation of risk management at the Casual Brezzy store, a reseller of imported Adidas shoes, using the ISO 31000 approach. MSMEs engaged in selling imported products face various risks, such as exchange rate fluctuations, supply delays, uncertainty regarding import regulations, and increasingly competitive markets. The research method used was descriptive qualitative, using interviews, observation, and documentation to identify, analyze, and evaluate risks based on the ISO 31000 framework. The results indicate that very high risks include delivery delays, regulatory compliance, exchange rate fluctuations, and tax burdens. Recommended risk mitigation measures include supplier diversification, strengthening internal control systems, optimizing cash flow, and improving compliance with import regulations. By consistently implementing ISO 31000 principles, MSMEs can improve operational resilience, business stability, and business sustainability.